2011
DOI: 10.1029/2011gl047652
|View full text |Cite
|
Sign up to set email alerts
|

Exact evaluation of gross photosynthetic production from the oxygen triple-isotope composition of O2: Implications for the net-to-gross primary production ratios

Abstract: The oxygen triple‐isotope composition of dissolved O2 provides an integrative method to estimate the rates of Gross Photosynthetic Production (GPP) in the upper ocean, and combined with estimates of Net Community Production (NCP) yields an estimate of the net‐to‐gross (NCP/GPP) production ratios. However, derivations of GPP from oxygen triple‐isotope measurements have involved some mathematical approximations. We derive an exact expression for calculating GPP, and show that small errors associated with approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(112 citation statements)
references
References 34 publications
5
105
0
2
Order By: Relevance
“…Mass spectrometer measurement procedure has been described in Juranek and Quay (2005 Mixed-layer 17 D-GOP rates were calculated using the approach outlined in Luz and Barkan (2011) and Prokopenko et al (2011) with terms added for horizontal and vertical advection as in Eqs. 5 and 6; horizontal advection terms were neglected for the Offshore region because horizontal surface 17 D diss gradients were typically less than the uncertainty of mixed-layer 17 D diss .…”
Section: Methodsmentioning
confidence: 99%
“…Mass spectrometer measurement procedure has been described in Juranek and Quay (2005 Mixed-layer 17 D-GOP rates were calculated using the approach outlined in Luz and Barkan (2011) and Prokopenko et al (2011) with terms added for horizontal and vertical advection as in Eqs. 5 and 6; horizontal advection terms were neglected for the Offshore region because horizontal surface 17 D diss gradients were typically less than the uncertainty of mixed-layer 17 D diss .…”
Section: Methodsmentioning
confidence: 99%
“…However, under certain conditions, this range may be exceeded and I have therefore chosen to cover a wider range of f and g values. For example, recent work by Prokopenko et al (2011) on gross oxygen production during a bloom in the coastal Bering Sea has found f values up to 1 and g values greater than 1.…”
Section: Input Parametersmentioning
confidence: 99%
“…There is currently no single universally-accepted method of calculating GOP, and many authors have argued that the ideal choice of parameters and constants may depend on properties of the system (e.g., the microbial species of interest and isotopic composition of oxygen in water, which is the source of photosynthetic O 2 ) (Luz and Barkan, 2000;Juranek and Quay, 2005;Reuer et al, 2007;Luz and Barkan, 2009;Stanley et al, 2010;Kaiser, 2011;Luz and Barkan, 2011;Nicholson et al, 2011;Prokopenko et al, 2011;Hamme et al, 2012). However, there is strong scientific consensus that calculations should be performed using the individual isotope ratios rather than the empirically defined term 17 ∆ which is a combination of two isotope ratios (Kaiser, 2011;Luz and Barkan, 2011;Nicholson et al, 2011;Prokopenko et al, 2011 as a supplement to this paper (Data set 2) so that GOP can be re-calculated in the future using new formulas (Kaiser, 2011). We also provide the MATLAB code used to calculate GOP, to ensure that the calculations in this paper can be reproduced by others.…”
Section: Calculation Of Nop From O 2 /Ar Mass Balancementioning
confidence: 99%
“…Because the triple oxygen isotope tracer is relatively new, advances in our theoretical understanding of the tracer are ongoing (Kaiser, 2011;Luz and Barkan, 2011;Nicholson et al, 2011;Prokopenko et al, 2011), as are improvements in measurement precision and accuracy Luz, 2003, 2011;Stanley et al, 2010).…”
Section: Oxygen As a Tracer Of The Biological Pumpmentioning
confidence: 99%